Etnoconhecimento sobre plantas medicinais e inter-relações com o meio ambiente na comunidade do Catu, Canguaretama (RN, Brasil) - Silva, Amanda Stefanie Sérgio da (2018)
Studies on ethno-cognitions are important for the understanding and appreciation of cultures, ways of acting and living with the environment. Medicinal plants are natural resources with properties capable of provoking beneficial reactions in the organism, used in the recovery and maintenance of well-being. The search for knowledge about plants and ecological relations has been carried out since ancient times. Due to the importance of local knowledge and the management of environmental resources for conservation, the present work has the objective of analyzing the system of ethnknowledge on medicinal plants, and discuss aspects and implications of the interrelationship with the biophysical and social environment of a population of the Brazilian Northeast, as a way of valuing the culture and the local plant wealth. Open and semi-structured interviews were conducted, following the Snowball method. A balance was sought between the ethical and ethical perspectives. The goal was to provide a hybridization between the knowledge of the interviewee and the researcher, generating intercientity. Samples of the plants were collected to assist in the identification of the species. Collections were performed with the help of the Guided Tour method, with random sampling. The ethnoecological approach used was based on the Kosmus-CorpusPraxis Complex analysis method. Based on the Content Analysis method, the quantifiable data were analyzed using a simple percentage, and the qualitative data were selected from the discourses for inductive conclusions. There were 68 species of plants, with a similar percentage between native and exotic. The most representative families were Fabaceae and Lamiaceae. The species with the highest number of citations were Rosmarinus officinalis L., Cymbopogon citratus (DC.) Stapf., Lippia alba (Mill.) N.E.Brown and Periandra mediterranea (Vell.) Taub. Leaves were the most used parts, consumed in the forms of teas and garrafadas, mainly in the treatment of respiratory diseases. The local experts of the Catu community have a great knowledge about medicinal plants and the ecological interactions that surround them. They have interrelationships with issues of faith, spirituality and respect for nature. The cultivation of medicinal plants in backyards helps in accessing these resources in times of emergency. The economy is based on subsistence and there are social relationships that help in obtaining medicinal plants. The results of this research are important for the valorization of the local culture and evidence the richness of plants with medicinal potential. This may reveal a rescue of traditional plant-use customs for the home-based manipulation of low-cost financial remedies for the entire community studied.